1974
DOI: 10.1039/c3974000943a
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected oxidation of a nitroxide alcohol with m-chloroperbenzoic acid

Abstract: Oxidation of 2,2,6,6-tetramethylpiperidin-4-01 forcing conditions, (2) becomes the principal product of the (la) with m-chloroperbenzoic acid in methylene chloride produces, in addition to the expected nitroxide (lb), varying amounts of 4-OXO-2, 2,6,6-tetramethylpiperidin-reaction (see Table ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…15 However, we found that the major product was alcohol 8 , 16 which could be obtained in about 50% yield using a larger excess of Raney Ni. We expected that, under similar conditions for preparation of Tempone ( 16 ), 17 oxidation of 8 using m -CPBA would provide 10 . Instead, we obtained 9 , 16 which was then oxidized further with Dess–Martin periodinane (DMP) to give ketone-nitroxide 10 .…”
mentioning
confidence: 99%
“…15 However, we found that the major product was alcohol 8 , 16 which could be obtained in about 50% yield using a larger excess of Raney Ni. We expected that, under similar conditions for preparation of Tempone ( 16 ), 17 oxidation of 8 using m -CPBA would provide 10 . Instead, we obtained 9 , 16 which was then oxidized further with Dess–Martin periodinane (DMP) to give ketone-nitroxide 10 .…”
mentioning
confidence: 99%
“…Desirable characteristics of these oxidations include the use of 1 mol % or less of the catalyst and only 1 equiv of the bulk oxidant and good selectivity for primary alcohols. Many different bulk oxidants have been used in this reaction including m -CPBA, , sodium hypochlorite, N -chlorosuccinimide, sodium bromite, [bis(acetoxy)iodo]benzene, high-valent metal salts, and electrooxidation. , The TEMPO-bleach oxidation developed by Anelli is the most useful for large-scale oxidations, although it does not work well with unsaturated alcohols. Our interest was drawn to the TEMPO-catalyzed m -CPBA oxidations 2,3 when we observed an unprecedented racemization of a chiral nitroxyl radical under similar conditions .…”
mentioning
confidence: 99%
“…The development of nitroxyl radical catalyzed peracid oxidations arose from Cella's report of an unexpected alcohol oxidation 2c. Cella found that the reaction was catalyzed by HCl and developed a convenient oxidation procedure using m -CPBA and 2,2,6,6-tetramethylpiperidinium hydrochloride (TMP·HCl) as the catalyst precursor 2a.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[22] bp 95ЊC/20 mm Hg. [23,24] 3-Carbamoyl-2,2,5,5-tetramethylpyrrolidine-1-oxyl. The general procedure was followed using 0.173 g (1 mmol) of 4-oxo-2,2,6,6-tetramethylpiperidine.…”
Section: -Cyclohexyl-4ј4ј-dimethyloxazolidinementioning
confidence: 99%